Activation of GPR15 and its involvement in the biological effects of smoking. Issue 11 (June 2017) - Kõks, Sulev; Kõks, Gea
Smoking is one of the most significant modifiable environmental risk factors for many diseases. Smoking causes excessive mortality worldwide. Despite decades of long research, there has not been a clear understanding regarding the molecular mechanism that makes smoking harmful to health. Some recent studies have found that smoking influences most significantly the expression and methylation of GPR15. GPR15 is an orphan receptor that is involved in the regulation of the innate immunity and the T-cell trafficking in the intestinal epithelium. Further studies have confirmed that GPR15 is very strongly involved in smoking and smoking-induced molecular changes. Therefore, the altered expression and epigenetic regulation of GPR15 could have a significant role in the health impact of smoking. Impact statement: The review describes an orphan receptor GPR15 that has recently been found to be influenced by smoking. This makes GPR15 very sensitive and adequate biomarker for smoking and smoking studies. Also, activation of GPR15 by smoking could help to explain its effects on health.